2014
DOI: 10.1128/jvi.00423-14
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Mutation (I1012F) of the RNA Polymerase of Marine Viral Hemorrhagic Septicemia Virus Changes In Vitro Virulence to Rainbow Trout Gill Epithelial Cells

Abstract: Viral hemorrhagic septicemia virus (VHSV) is separated into four different genotypes (I toIV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
(56 reference statements)
3
35
0
Order By: Relevance
“…Previously, it was shown that the G protein is a determinant for temperature sensitivity and it was suggested that the polymerase complex would be involved, but it was not studied (Biacchesi et al, 2002;Biacchesi, 2011). In this study, we interchanged the L protein gene between two strains of VHSV, JF-09 with an ability to grow at higher temperature (Kim et al, 2014) and MI03GL, a Great Lakes strain, (Ammayappan and Vakharia, 2009) sensitive to temperatures above 18 • C. These strains belong to genotype IVa and IVb, respectively. Here, we demonstrate the gain-and loss-of-function of VHSV titers at different temperatures using reverse genetics approach.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Previously, it was shown that the G protein is a determinant for temperature sensitivity and it was suggested that the polymerase complex would be involved, but it was not studied (Biacchesi et al, 2002;Biacchesi, 2011). In this study, we interchanged the L protein gene between two strains of VHSV, JF-09 with an ability to grow at higher temperature (Kim et al, 2014) and MI03GL, a Great Lakes strain, (Ammayappan and Vakharia, 2009) sensitive to temperatures above 18 • C. These strains belong to genotype IVa and IVb, respectively. Here, we demonstrate the gain-and loss-of-function of VHSV titers at different temperatures using reverse genetics approach.…”
mentioning
confidence: 93%
“…First we propagated five different VHSV strains (DK-3592B; Ia, 1p8; Ib, NO/650/07; III, JF-09; IVa, and MI03GL; IVb) in Epithelioma papulosum cyprini (EPC) cells at 15 • C, in line with previous studies (Ammayappan and Vakharia, 2009;Kim et al, 2014). All strains were also used to infect EPC cells at 23 supernatants were collected and titrated on EPC cells (Karber, 1931).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Historically, the virulent strains were thought to originate from avirulent strains circulating among wild marine fish before spreading through the trade of infected fish. It was surmised that a few mutations were responsible for changes from low to high virulence [125,126]. However, it has not been established whether these virulent variants preexisted in wild fish or if they arose and were selected in farmed trout.…”
Section: Applications Of Ngs To Fish Virology: Some Successful Examplesmentioning
confidence: 99%
“…Rhabdoviridae (Kim et al, 2014), Filoviridae (Ebihara et al, 2006) and Bornaviridae (Ackermann et al, 2007). This Cterminal component of L proteins of NNS RNA viruses, especially the region between domains V and VI, is highly variable, and considered as a domain of L which interacts with unique host cell transacting transcriptional cofactors (Dortmans et al, 2011;Poch et al, 1990;Sidhu et al, 1993).…”
mentioning
confidence: 99%